The Meaning of the Kupatan Tradition for the Islamic Community of the Coastal Village of Sedayulawas, Lamongan - Alfin Wardah Royyanah; Adib Fatoni; Yuldashev Azim Abdurakhmonovich (International Journal of Religion and Social Community, 2025)
This study was motivated by the author's curiosity about the Kupatan tradition practised by the community of Sedayulawas Village, Lamongan, as a form of a second holiday in the month of Shawwal, one week after Eid al-Fitr. The purpose of this study was to find out how the Kupatan tradition is practised in Sedayulawas Village, which is quite interesting and unique. In addition, it also aims to find out the community's perspective on the meaning of the Kupatan tradition in their lives in general. The results of the study show that the Kupatan tradition, which is carried out every year by the people of Sedayulawas Lamongan Village, is quite interesting because the traditional celebration or Kupatan Day is celebrated by having fun while eating ketupat and lepet as symbols of Kupatan. This research was conducted using qualitative methods, whereby the author endeavoured to understand the implementation of the Kupatan tradition carried out by the community of Sedayulawas Village, which has been passed down from generation to generation. This research was conducted entirely by the author based on facts and data obtained from observations and interviews. Thus, this research is descriptive qualitative research, so that all understandings, explanations, and findings are described or explained in the form of sentences as the results of critical and argumentative interpretations based on research data.